Computed tomographic reference ranges of intrathoracic caudal vena cava ratios in sedated adult dogs without cardiac, pulmonary, or hypovolemic disease - Jacqueline N. Sankisov; Lauren Newsom (Veterinary Medicine and Science, 2024)
Abstract Background Radiographic assessment of the intrathoracic caudal vena cava (CVC) is commonly used to evaluate hemodynamic status in veterinary patients without and with pulmonary, pericardial, or right‐sided cardiac diseases. Many of these patients are now commonly evaluated with computed tomography (CT) in both emergency and referral settings. Traditional radiographic ratios in dogs, particularly the CVC height/aorta height (CVC/Ao) ratio, are often extrapolated to CT in order to determine if the CVC is normal in size. Objectives The first goal of this retrospective study was to create an objective measurement method to evaluate the size of the CVC via CT. The second goal was to report normal CVC ratio values in both sagittal and transverse CT images. Methods The traditional lateral radiographic CVC ratios were extrapolated to similar ratios obtained from sagittal CT images in stable, sedated adult canine patients without known cardiac or pulmonary disease. Additionally, new methods of canine CVC ratios using transverse CT images were defined using vessel height and area. Mean, standard deviation, and 95% confidence intervals (CIs) of the CVC ratios in transverse and sagittal CT images were calculated to determine normal reference ranges. Results Ratio agreement from observers of different skill levels was moderate to excellent. Sagittal CT CVC/Ao mean was 1.07 ± 0.17 with a CI of 0.71.42. The mean and CI of transverse CT CVC/Ao height and area were 1.14 ± 0.27 and 0.781.44 and 1.36 ± 0.59 and 0.641.94, respectively. Conclusions Application of normal sagittal and transverse CT ratio values in canine patients with and without hypotension, pulmonary, pericardial, or right‐sided cardiac diseases is necessary to determine the clinical usefulness of these ratios.